ФУНДАМЕНТ ПЛАТФОРМ И ЕГО НЕФТЕГАЗОНОСНОСТЬ - Летавин А.И. (My University, 2002)
Обосновывается вторичный характер залежей УВ в породах фундамента. Устанавливается связь нефтегазоносности фундамента с нефтегазоматеринской толщей, развитой в перекрывающих фундамент платформенных отложениях. Утверждается, что за пределами зоны развития нефтематеринских пород фундамент бесперспективен. Зоны непосредственного контакта нефтегазоматеринских пород с фундаментом наиболее перспективны для поисков залежей УВ.

There is grounded secondary character of hydrocarbon accumulations in rocks of basement. There is ascertained relation of the basement oil-gas bearing capacity with area spacing of source rock series in the cover. It asserted that there are no prospects of the basement outside spacing bounds of source rocks. Direct contact zones of oil-gas source rocks with the basement are the most prospective ones for prospecting of HC accumulations in the basement.
Keywords: 551.242.5;552.578.2.061.32/33